Zinc sulfate supplementation of cultured peripheral blood Lymphocytes: genomic instability related to its deficiency and excess - Padula, Gisel (2014)
Zinc (Zn) plays a vital role in children growth and is involved in DNA synthesis and maintenance processes. The current nutrient intake recommendations do not consider the levels required for maintaining genomic stability. The objective of this study is to analyze the cytotoxic and genotoxic effect of in vitro Zn supplementation to evaluate deficiency and excess, and the concentrations within the normal physiological range established for children (80-280 µg/dl). To achieve Zn deficiency, the HAMF12 medium (HF12) was chelated (HF12Q). Lymphocytes were isolated from healthy donors and cultured for 7 days: 1-control (HF12, 60 µg/dl SO4 Zn); 2-deficient (HF12Q, 0 µg/dl SO4 Zn); 3-80 (HF12Q + 80 µg/dl SO4 Zn); 4-180 (HF12Q + 180 µg/dl SO4 Zn); 5-280 (HF12Q + 280 µg/dl SO4 Zn); 6-380 (HF12Q + 380 µg/dl SO4 Zn). Comet and micronucleus assays were performed, and cell viability was determined. Differences were evaluated with χ2 and ANOVA (p<0.05). The DNA damage index (comet assay) was significantly higher in the deficient culture respect to the others. Only the 380 µg/dl dose showed significantly increased frequency in DNA damage in relation to the other supplemented cultures. Micronuclei frequency was significantly higher in the deficient, 280 and 380 µg/dl cultures in comparison with the control, 80 and 180 µg/dl. The higher frequency of chromosomal damage was observed at 380 µg/dl SO4 Zn. In vitro Zn supplementation reduced genomic instability. Supplementation with Zn at 80 µg/dl and 180 µg/dl proved to be the most beneficial in reducing genomic instability, whereas doses of 280 and 380 µg/dl would cause an increase in DNA damage.